Microbiological and Biochemical Tests on Tempe Production Using Tempe Mold Innovation - Siti Harnina Bintari; Dhimas Fajar Eka Purnama; Danang Dwi Saputro; Sunyoto Sunyoto; Pramesti Dewi; Ibnul Mubarok (Biosaintifika: Journal of Biology & Biology Education, 2022)
Tempe is a popular fermented food in Indonesia, one of the important things in the process of making tempeh is the tempe incubation container. The purpose of this study was to prove the quality of tempe products made using the tempe mold innovation suitable for production, to analyze the comparison between the quality of tempe products made using a tempe incubation tool and without using the tool. Experimental research with Completely Randomized Design (CRD), applying a tempe incubator and without using a tool as a control. Test methods used include testing water content, hygiene, number of mold colonies and protein content. Based on the results of the study, tempe products made using a tempe printer contain a moisture content of 51.4 - 56.2%, protein content 17.92 - 18.58%, the number of mold colonies 3.65 x 105 untill 4.08 x 105 cell/gr and negative Escherichia coli. Based on the results of the study, it was concluded that the tempe products made using the tempe mold innovation tool had met the biological and chemical quality standards based on SNI 3144:2015 and had an overall quality test result that was superior to the control.